Leukocyte Adhesion Defect Type 1. Reporting Patient Series and their Survival Without Bone Marrow Transplantation - Omar Abuzaitoun; Husni Maqbuol; Hasan Fitian; Hikamt Al Sae’ed (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The survival of patients suffering from severe LADI is discussed in this paper. The approach is to do bone marrow transplantation as soon as possible, however, we report 4 patients suffering from severe LADI, who did not have bone marrow transplantation. We report the favorable outcome with conservative treatment (prophylactic antibiotics)